School, Hygienic care and education. The contribution of Achille Sclavo - Giambattista Bufalino (Firenze University Press, 2020)
In the late nineteenth and early decades of the twentieth century, a firm alliance between hygiene and education has been promoted as an important means of developing health in childhood. Hygienists, social reformers and educators were the main impetus for the development of a hygienic awareness while the school was at the center of the so-called pedagogisation of the body, that is a systematic educational action aimed at educating the body. Within this context, this article centers on the pedagogical efforts of Achille Sclavo (1861-1930), an internationally renowned hygienist, with the aims of reconstructing his pedagogy and educational work, thus discussing his views on hygienic education which were indicative of attitudes, beliefs, and ideas of his time. This is an attempt to shed light on an unknown aspect of his life and to offer an original perspective from which to explore the link between hygienic education and educational innovation.